2002
DOI: 10.1007/s00335-001-2101-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and mapping of ATOH7, a human atonal homolog with a predicted role in retinal ganglion cell development

Abstract: The human ATOH7 gene encodes a basic helix-loop-helix (bHLH) transcription factor that is highly similar to Drosophila Atonal within the conserved bHLH domain. The ATOH7 coding region is contained within a single exon. We mapped ATOH7 to Chromosome (Chr) 10q21.3-22.1, a region syntenic to the segment of mouse Chr 10 where Atoh7 (formerly Math5) is located. The evolutionary relationship between ATOH7 and other atonal homologs was investigated using parsimony analysis. A direct comparison of ATH5/7 and ATH1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 67 publications
0
50
2
Order By: Relevance
“…In the upstream region of Math5, two highly conserved regions among the Xenopus, mouse and human Ath5 genes are shown (yellow boxes in Fig. 7A) (Brown et al, 2002;Hutcheson et al, 2005;Riesenberg et al, 2007). Within these two evolutionarily conserved regions are four E-boxes, bHLH consensus binding sites (blue boxes) (Murre et al, 1989;Hutcheson et al, 2005).…”
Section: Regulation Of Math5-gfp1mentioning
confidence: 99%
“…In the upstream region of Math5, two highly conserved regions among the Xenopus, mouse and human Ath5 genes are shown (yellow boxes in Fig. 7A) (Brown et al, 2002;Hutcheson et al, 2005;Riesenberg et al, 2007). Within these two evolutionarily conserved regions are four E-boxes, bHLH consensus binding sites (blue boxes) (Murre et al, 1989;Hutcheson et al, 2005).…”
Section: Regulation Of Math5-gfp1mentioning
confidence: 99%
“…Other vertebrate Ath5 genomic sequences were identified as follows: X. tropicalis (http://genome.jgi-psf.org/xenopus0/ xenopus0.home.html); mouse and human Ath5 (Atoh7) have been previously isolated and aligned (Brown et al, 2002); chick (GenBank Number AJ630209) (Skowronska-Krawczyk et al, 2004); Fugu (scaffold 1775; http://genome.jgi-sf.org/fugu3/fugu3.home.html); and zebrafish (clone AL627094; http://trace.ensembl.org/perl/ssahaview). The genomic sequence for Drosophila atonal was derived from BAC clone #AC008094 (http://flybase.bio.indiana.edu/).…”
Section: Sequence Analysismentioning
confidence: 99%
“…The cloned sequence accurately reproduces the activity and the mode of regulation of the endogenous promoter. It contains essential regulatory elements that are well conserved across distant vertebrate species (Brown et al, 2002;Hutcheson et al, 2005;Skowronska-Krawczyk et al, 2004), but it is unclear whether the different species use similar strategies to regulate ATH5 expression. Whereas a proximal cis-regulatory region of the Xenopus Xath5 gene suffices, much as in the chick retina, to drive retina specific reporter gene expression in a bHLHdependent manner, the mouse ATH5 promoter appears to be regulated differently (Hutcheson et al, 2005).…”
Section: Spatiotemporal Progenitor Patterning and Rgc Genesismentioning
confidence: 99%
“…Initially cloned and analysed in Xenopus (Kanekar et al, 1997), its mouse (Brown et al, 1998), zebrafish (Masai et al, 2000), chicken (Liu et al, 2001;Matter-Sadzinski et al, 2001) and human (Brown et al, 2002) orthologues have also been identified. In the mouse, In the developing retina, the production of ganglion cells is dependent on the proneural proteins NGN2 and ATH5, whose activities define stages along the pathway converting progenitors into newborn neurons.…”
Section: Introductionmentioning
confidence: 99%